Superior growth performance in broiler chicks fed chelated compared to inorganic zinc in presence of elevated dietary copper. Issue 1 (December 2016) - Zhao, Junmei; Shirley, Robert; Dibner, Julia; Wedekind, Karen; Yan, Frances; Fisher, Paula; Hampton, Thomas; Evans, Joseph; Vazquez-Añon, Mercedes
Abstract Background The goal of this study was to compare the antagonism of elevated dietary Cu (250 mg/kg) from CuSO4 on three different Zn sources (ZnSO4 · H2 O; [Zn bis(−2-hydroxy-4-(methylthio)butanoic acid)], Zn(HMTBa)2, a chelated Zn methionine hydroxy analogue; and Zn-Methionine), as measured using multiple indices of animal performance in ROSS 308 broilers. Methods Three experiments were conducted in broiler chicks fed a semi-purified diet. All birds were fed a Zn-deficient diet (8.5 mg/kg diet) for 1 wk, and then provided with the experimental diets for 2 wks. Results Experiment 1 was a 2 × 2 factorial design with two levels of Cu (8 vs. 250 mg/kg diet from CuSO4 ) and two Zn sources at 30 mg/kg [ZnSO4 · H2 O vs. Zn(HMTBa)2 ]. Elevated Cu impaired growth performance only in birds fed ZnSO4 . Compared to ZnSO4 · H2 O, Zn(HMTBa)2 improved feed intake (12 %;P < 0.001) and weight gain (12 %, P < 0.001) and the benefits were more pronounced in the presence of 250 mg/kg diet Cu. Experiment 2 was a dose titration of ZnSO4 · H2 O and Zn(HMTBa)2 at 30, 45, 60, and 75 mg/kg diet in the presence of 250 mg/kg CuSO4 . Feed:gain was decreased and tibia Zn was increased with increasing Zn levels from 30 to 75 mg/kg. Birds fed Zn(HMTBa)2 consumed more food and gained more weight compared to birds fed ZnSO4, especially at lower supplementation levels (30 and 45 mg/kg; interactionP < 0, 05). Experiment 3 compared two organic Zn sources (Zn(HMTBa)2 vs. Zn-Methionine) at 30 mg/kg with or without 250 mg/kg CuSO4 . No interactions were observed between Zn sources and Cu levels on performance or tissue mineral concentrations. High dietary Cu decreased weight gain (P < 0.01). Tibia Cu and liver Cu were significantly increased with 250 mg/kg dietary Cu supplementation (P < 0.01). No difference was observed between the two Zn sources. Conclusions Dietary 250 mg/kg Cu significantly impaired feed intake and weight gain in birds fed ZnSO4 · H2 O, but had less impact in birds fed Zn(HMTBa)2 . No difference was observed between the two organic zinc sources. These results are consistent with the hypothesis that chelated organic Zn is better utilized than inorganic zinc in the presence of elevated Cu.